Understanding malaria transmission in the Amazon : the role of land use/land cover interactions, biological diversity, and climate - Daza, William Gonzalez (2023)
This work addresses the issue of malaria transmission in the Amazon, specifically in the region of Brazil and Colombia. Chapter 1 focuses on the Brazilian Amazon, analyzing the spatial pattern and the relationship between malaria risk in each municipality in the legal Amazon and environmental factors such as climate, land use, biodiversity and landscape configuration between the years 2007 and 2018. The study found that areas with low diversity of endemic species and high changes in natural cover have a higher risk of malaria transmission. The research highlights the importance of considering the broader ecological context in malaria control efforts such as landscape configurations (contact zones between the vector and the human population) and biodiversity as an important point for the reduction of malaria. Chapter 2 focuses on the municipality of La Pedrera - Amazonas, Colombia, and uses a Ross MacDonald SIR model to analyze ecoepidemiological parameters and the impact of delays in precipitation time, temperature and changes in land use on malaria transmission. The study found that changes in land use between 2007 and 2020, including increases in forested areas, urban infrastructure and edges of water bodies, resulted in a steady increase in the carrying capacity of mosquitoes. The levels of temperature and precipitation presented consistent variations that aligned with the rainy and dry seasons, respectively, being strongly influenced by the climatic phenomenon known as ENSO. The results suggest that high precipitation and temperature increase the risk of malaria infection in the following two months, influenced by secondary vegetation and urban infrastructure close to primary forest formations or edges of water bodies. Overall, this thesis contributes to a better understanding of the factors that influence malaria transmission in these regions and provides tools based on observation of climate and land use that may be useful for public health authorities and policy makers in developing malaria control effective strategies.